Efficacy of Probiotic and Nitrifier Bacterial Consortium for the Enhancement of Litopenaeus Vannamei Aquaculture - R Karthik; Angelin C Pushpam; Yashika Chelvan; Vanitha MC (International Journal of Veterinary Science and Research - Peertechz Publications, 2016)
Shrimp farming is one of the most important aquaculture practices worldwide. In general, the excess feed and faecal matter deposited in the bottom of the pond undergo ammonification and result in excess of ammonia formation in pond water and sediment. In addition, eutrophication in the culture system/pond can cause stress to the animals and ultimately end with microbial diseases. The present simulation study was carried out to isolate the potential beneficial bacterial strains to improve the shrimp micro biota (GIT) and to reduce the ammonia and nitrite toxicity in shrimp grow out ponds on a laboratory scale experiment. The Lactobacillus sp AMET1506 obtained from AMET Microbial Culture Collection Centre, showed strongest antibacterial activity against shrimp pathogens. The Nitrosomonas sp AMETNM01 and Nitrobacter sp AMETNB03 were isolated from shrimp culture pond sediments using Winogradsky Phase I and Phase II  medium. A total of 150 shrimps (Litopenaeus vannamei) PL (15) were obtained from a commercial shrimp hatchery located in Marakanam, Kanchipuram District, Tamil Nadu, India. After acclimation of the shrimps for seven days, the average weight of the shrimps were divided into three batches in 100 litre glass tanks (70 liter of seawater), each containing 50 post larvae. The Tank 1 was treated with commercial feed and the Tank 2 and 3 were treated through feed supplemented with 105 CFU g-1 of Lactobacillus sp AMET1506 for 40 days. After 30 days of culture, in tank 3 the ammonia and nitrite oxidizing bacterial strains such as, Nitrosomonas sp AMETNM01 and Nitrobacter sp AMETNB03 strains (each in the range of 105 ml-1) were added (only once on the 31st day) and the Ammonia (NH4 +), Nitrite (NO2) Nitrate (NO3) in the all the tank water were analyzed from 31st day up to 40th day. The shrimp survival (%), Individual Weight (wt/pcs) and the microbial load revealed that the tank 3 (Combination of Lactobacillus sp AMET1506, Nitrosomonas sp AMETNM01 and Nitrobacter sp AMETNB03) was found to be superior comparatively in probiotics than other two tanks. The present study suggests that, the use of beneficial bacterial strains in shrimp culture could prevent the aquaculture pond from undergoing eutrophication and control the shrimps from microbial diseases and ultimately enhance the production.